2019
DOI: 10.1111/ffe.13045
|View full text |Cite
|
Sign up to set email alerts
|

Ratcheting‐fatigue behaviour of bainite 2.25Cr1MoV steel with tensile and compressed hold loading at 455°C

Abstract: The ratcheting behaviour of a bainite 2.25Cr1MoV steel was studied with various hold periods at 455°C. Particular attention was paid to the effect of stress hold on whole‐life ratcheting deformation, fatigue life, and failure mechanism. Results indicate that longer peak hold periods stimulate a faster accumulation of ratcheting strain by contribution of creep strain, while double hold at peak and valley stress has an even stronger influence. Creep strains produced in peak and valley hold periods are noticeable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 52 publications
(104 reference statements)
3
5
0
Order By: Relevance
“…The primary creep stage of 2.25Cr-1Mo steel is quite short. This feature was also observed under the ratcheting-fatigue tests of 2.25Cr-1Mo-V steel [28]. Subsequently, the strain accumulation rate quickly decreases and remains constant after entering the secondary creep stage.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…The primary creep stage of 2.25Cr-1Mo steel is quite short. This feature was also observed under the ratcheting-fatigue tests of 2.25Cr-1Mo-V steel [28]. Subsequently, the strain accumulation rate quickly decreases and remains constant after entering the secondary creep stage.…”
Section: Resultssupporting
confidence: 61%
“…As such, the cyclic creep data of bainite 2.25Cr-1Mo-V steel at 455 • C can be used to further check the suitability of the proposed model. For the case of a short-term duration of hold stress and a negative stress ratio, the blue square points of Figure 12 present the comparison of the predicted and experimental results in the work of Zhao et al [28]. It appears that all the predicted results fall within a scatter band of ±1.5.…”
Section: Modified Life Prediction Considering Anelastic Recoverymentioning
confidence: 81%
“…It is necessary to extend the scope of tests so that each load cycle will be characterized by the presence of both constant and variable loads. An example of such research is described, inter alia, in [ 4 ], in terms of deformation. Progress in low-cycle fatigue research, especially in the field of testing machine control abilities, opens up a wide range of possibilities for describing the low-cycle fatigue process in terms of energy.…”
Section: Discussionmentioning
confidence: 99%
“…Creep is also listed as one of the possible fatigue damage modes because cyclic creep of the material changes the nature of the load and the durability of the objects. In such a case, predicting the fatigue life based on the commonly used fatigue characteristics may lead to divergence between the experimental and predicted results [ 4 ]. In works [ 5 , 6 ], based on constant-amplitude tests, it was shown that the fatigue life of the samples under the conditions of constant stress amplitude ( ) is lower than that obtained in the conditions of controlled deformation ( ).…”
Section: Introductionmentioning
confidence: 99%
“…The primary creep stage of 2.25Cr-1Mo steel is quite short, and this feature has also been observed under the ratcheting-fatigue tests of 2.25Cr-1MoV steel. 34 However, the strain accumulation rate quickly decreases afterwards and keeps constant after entering the secondary creep stage, of which the constancy result from the equilibrium condition between strain hardening and recovery softening. The secondary creep stage accounts for nearly 80% of the endurance life and is also referred to as the stable stage.…”
Section: Cyclic Test Programmentioning
confidence: 99%